Pendidikan Seni melalui Inovasi Desain, Kewirausahaan, dan Pemasaran Produk Kerajinan Bambu di Kalurahan Bawuran - Agung Wicaksono; Arif Suharson; Anom Wibisono; Lilik Ambarwati; Meidi Syaflan; Prafidhya Dwi Yulianto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The research objective of the art innovation dissemination programme for bamboo craft groups in Kalurahan Bawuran, Pleret, Bantul, Yogyakarta is to create new designs and marketing of bamboo products in the digital era to improve the economic welfare of the community through art education and technical training. Bamboo products in Kalurahan Bawuran are a legacy of skills passed down from generation to generation. Bamboo raw materials are obtained from the local area, but often the quality of bamboo is poor, monotonous designs and product marketing are still a problem for crafters. Crafters do not yet have an efficient production system to produce products with optimal quality and marketing capacity. The urgency of this research is to improve the quality of renewable designs with better machine technology, so that bamboo furniture products can penetrate the global market. The 30 selected craftsmen involved were equipped with business management, entrepreneurship, and digital marketing. This qualitative research uses an aesthetic method with a practice-based research approach carried out with the stages of literature research, empiric study, visual research, and practice. The aesthetics of new bamboo craft creations have an impact on the preservation of sustainable local artistic creations that are able to meet the needs of the global era. This research produced 3 sets of functional products and 1 new design gazebo with an impact on economic improvement with business management methods (entrepreneurship and modern marketing) which are expected to be a means of environmentally sound education and regeneration of creative craftsmen as an entity that must be maintained, preserved, and developed according to the demands of the times.